Tribocorrosion behaviour of ZrOxNy thin films for decorative applications - Ferreira, S. C. (2006)
The aim of this work is the investigation of the tribocorrosion behaviour of single layered zirconium oxynitride, ZrOxNy, thin films in 11 reciprocating sliding and immersed in an artificial sweat solution at room temperature. During the wear tests samples were kept under 12 potentiostatic control and the corrosion current were monitored. Also, Electrochemical Impedance Spectroscopy (EIS) tests were performed before 13 and after sliding in order to evaluate, in detail, the modification of the protective character of the coating caused by the joint action of wear and 14 corrosion. The modifications of the coating structure and microstructure and/or chemical composition originated by the variation of the deposition 15 parameters were also evaluated and correlated with the corrosion mechanisms occurring in each system